Islam and Bioethics - Sandhya Bhattacharya (International Institute of Islamic Thought, 2006)
On 27-28 March 2006, Pennsylvania State University hosted an international conference on “Islam and Bioethics: Concerns, Challenges, and Responses.” Cosponsored by several academic units in the College of Liberal Arts, the conference brought in historians, health care professionals, theologians, and social scientists from ten different countries. Twenty-four papers were presented, along with Maren Grainger-Monsen’s documentary about an Afghani immigrant seeking cancer treatment in California. After opening remarks by Susan Welch (dean, College of Liberal Arts) and Nancy Tuana (director, Rock Ethics Institute), panelists analyzed “Critical Perspectives on Islamic Medical Ethics.” Hamada Hamid’s (New York University Medical School) “Negotiating Autonomy and Religion in the Clinical Setting: Case Studies of American Muslim Doctors and Patients,” showed that few doctors explore the role of religion in a patient’s decision-making process. She suggested that they rethink this practice. Hassan Bella (College of Medicine, King Faisal University, Dammam) spoke on “Islamic Medical Ethics: What and How to Teach.” His survey, conducted in Saudi Arabia among medical practitioners, revealed that most practitioners approved of courses on Islamic ethics but did not know if such courses would improve the doctor-patient relationship. Sherine Hamdy’s (Brown University) “Bodies That Belong to God: Organ Transplants and Muslim Ethics in Egypt” maintained that one cannot easily classify transplant patients’ arguments as “religious” or “secular,” for religious values are fused together with a patient’s social, political, and/or economic concerns. The second panel, “Ethical Decision-Making in Local and International Contexts,” provoked a great deal of discussion. Susi Krehbiel (Brown University) led off with “‘Women Do What They Want’: Islam and Family Planning in Tanzania.” This ethnographic study was followed by Abul Fadl Mohsin Ebrahim’s (KwaZulu University, Durban) “Human Rights and Rights of the Unborn.” Although Islamic law is commonly perceived as antagonistic to the UN’s charter on human rights, Ebrahim argues that both may be used to protect those who can and cannot fight for their right to dignity, including the foetus. Thomas Eich (Bochum University) asserted in “The Process of Decision Making among Contemporary Muslim Religious Scholars in the Case of ‘Surplus’ Embryos” that decisions reached by international Muslim councils were heavily influenced by local politics and contentious decisions in such countries as Germany and Australia. The afternoon panel, “The Fetus and the Value of Fetal Life,” focused on specific issues raised by artificial reproductive technologies (ARTs). Vardit Rispler-Chaim (Haifa University) presented “Contemporary Muftis between Bioethics and Social Reality: Pre-Selection of the Sex of a Fetus as Paradigm.” After summarizing social customs and religious literature from around the world, she claimed that muftis generally favor pre-selection techniques and suggested that their reasoning is guided by a general social ...